2015
DOI: 10.1016/j.echu.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Radiology Undergraduate and Resident Curricula: A Narrative Review of the Literature

Abstract: ObjectiveThe purpose of this study was to examine the literature regarding radiology curricula for both undergraduates and residents.MethodsA review of the literature was performed using relevant key words. Articles were retrieved through December 2012 using PubMed, ScienceDirect, ERIC, Proquest, and ICL databases along with a manual review of references.ResultsOf the 4716 unique abstracts reviewed by the author, 142 were found to be relevant to the purpose of this study. Undergraduate radiology education, rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 126 publications
0
20
0
Order By: Relevance
“…Additionally, the use of a deductive approach is advised. In many faculties, medical image perception training is provided when students already have acquired some knowledge on anatomy and pathophysiology …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of a deductive approach is advised. In many faculties, medical image perception training is provided when students already have acquired some knowledge on anatomy and pathophysiology …”
Section: Discussionmentioning
confidence: 99%
“…On average 5% of total teaching time is dedicated to radiology (Heptonstall et al, 2016) and only 15% of medical schools have a formal radiology curriculum in place (Bhogal et al, 2012). The same variability is found across Europe (Ischerwood and Thomsen, 1993;Lass and Scheffler, 2003;Kourdioukova et al, 2011) and the United States (Gunderman et al, 2003;Barzansky and Etzel, 2004;Linaker, 2015). In the United Kingdom, it has been reported that junior doctors feel radiology teaching at medical school is unstructured and insufficient, ultimately resulting in them being unprepared for work (Nyhsen et al, 2011(Nyhsen et al, , 2013, with similar findings in Canada (Dmytriw et al, 2015) and New Zealand (Subramaniam et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Many studies have found that medical undergraduates perceive radiology to be an important aspect of education (Boissonnault et al, 2014;Linaker, 2015). However, the amount of time given to teaching radiology to medical students in the United Kingdom varies widely (Kalami et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Students spend up to 35 hours a week in the classroom. [2][3][4][5][6] Students experience stress for many reasons, such as financial issues, fatigue, length of time in the program, and stress levels have been linked to sex. 2,3 Students are required to pass high stakes exams to obtain licensure.…”
Section: Introductionmentioning
confidence: 99%
“…''However, a dearth of literature exists examining how radiology is taught, learned, or evaluated.'' 4 The overriding issue that guides most instructors is whether material is clinically important for students to master. It is important to remain focused on the needs of the students and what they should know to practice competently.…”
Section: Introductionmentioning
confidence: 99%